2019
DOI: 10.22319/rmcp.v10i3.4667
|View full text |Cite
|
Sign up to set email alerts
|

Yield, agronomic parameters and nutritional quality of Tithonia diversifolia in response to different fertilization levels

Abstract: La Tithonia diversifolia es una planta que ha demostrado una alta producción de biomasa y rápida recuperación después del corte, con altos valores bromatológicos especialmente en proteína; esto la convierte en un material con alto potencial genético como alternativa para la alimentación animal. Se realizó una investigación con el fin de determinar la respuesta de la planta a diferentes niveles de fertilización; para ello se estableció un experimento en un diseño de bloques completos al azar con seis tratamient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 4 publications
1
6
0
11
Order By: Relevance
“…Similarly, the consumption of grasses that are less lignified has a clear effect on ruminal digestibility and passage rate (O'Mara 2004). Thus, Blaxter and Clapperton (1965) reported that by decreasing the digestibility of forages from 75% to 55%, the emission of methane increases from 306 to 499 g day -1 . Lower fibre content and higher CP content could explain the decrease in CH 4 production found in this study with the inclusion of T. diversifolia in a basal diet of U. brizantha or another tropical pasture.…”
Section: Methane Productionmentioning
confidence: 99%
“…Similarly, the consumption of grasses that are less lignified has a clear effect on ruminal digestibility and passage rate (O'Mara 2004). Thus, Blaxter and Clapperton (1965) reported that by decreasing the digestibility of forages from 75% to 55%, the emission of methane increases from 306 to 499 g day -1 . Lower fibre content and higher CP content could explain the decrease in CH 4 production found in this study with the inclusion of T. diversifolia in a basal diet of U. brizantha or another tropical pasture.…”
Section: Methane Productionmentioning
confidence: 99%
“…These weights were similar to those reported by Gallego et al (2015) in Colombia under conditions similar to those given in environment 3, and where Ruiz et al (2013) recorded weights of 100 green leaves between 110 and 190 g at 42 days, and between 150 and 240 g at 60 days. Botero et al (2019) found a positive response of T. diversifolia when it was fertilized. The response found by these authors was greater than that reported in this study (2.5 times more DW when T. diversifolia was fertilized).…”
Section: Indicatedmentioning
confidence: 94%
“…Marandú in environment 1 and 2 and Cenchrus clandestinus in environment 3 were used as the reference for comparison with local feed supply. The level of fertilization used in environment 1 was in accordance with the extraction of nutrients of 40 days old T. diversifolia plants (Botero et al 2019). These nutrients were applied by fertilizing with urea (46% N), ammonium phosphate (DAP) [(NH 4 ) 2 HPO 4 ; 46% P 2 O 5 , 18% N] and potassium chloride (KCl, 60% K 2 O) at a fertilizer rate of 16.22 g/plant (324 kg/ha), 2.15 g/plant (43 kg/ha) and 4.89 g/plant (98 kg/ha) respectively.…”
Section: Experimental Designmentioning
confidence: 99%
“…El contenido de PC encontrado en las especies estudiadas podría atribuirse a su capacidad de adaptación para aprovechar los nutrientes del suelo y al manejo agronómico (Botero et al, 2019;Edwards et al, 2012;Gómez et al, 2015). Cabe mencionar que en este estudio todas las especies fueron establecidas por semilla sexual, lo cual permite un mejor desarrollo del sistema radicular (raíz pivotante) y, en consecuencia, una mayor capacidad para realizar una absorción de nutrientes que cuando se establecen plantas por estaca (Saavedra, 2016).…”
Section: Proteína Crudaunclassified
“…Cabe mencionar que en este estudio todas las especies fueron establecidas por semilla sexual, lo cual permite un mejor desarrollo del sistema radicular (raíz pivotante) y, en consecuencia, una mayor capacidad para realizar una absorción de nutrientes que cuando se establecen plantas por estaca (Saavedra, 2016). De igual modo, la altura y la frecuencia de corte pudieron haber tenido un efecto sobre el contenido de PC, ya que, a menor edad y altura de corte, mayor contenido de PC (Botero et al, 2019;Edwards et al, 2012;Rodríguez & Roncallo, 2013), en tanto a medida que envejece la planta, la pared celular aumenta y el contenido celular disminuye (Apraéz et al, 2012). En este caso particular, pese a la pobre calidad de los suelos de la zona, los porcentajes de PC observados en las tres especies son elevados en comparación con los estudios citados, que corresponden a zonas con mejores condiciones edácas; esto sugiere que T. diversifolia, G. sepium y C. cujete poseen una buena capacidad de adaptación y aprovechamiento de nutrientes.…”
Section: Proteína Crudaunclassified